What Justice? Whose justice?: Rethinking climate justice through climate change impacts and options for adaptation in Africa - Mugambiwa, Shingirai Stanely (Technium Social Sciences Journal, 2021)
Climate change is considered a justice issue based on the causes of the phenomenon, its impacts and polices designed to manage it. Previous studies have revealed that Africa and the entire developing world contribute less to Green House Gas emissions (GHG) which is the leading cause of climate change, but they suffer the most from its consequences, whereas the first world, whose contribution to GHG is immense but the impact of the phenomenon to them is minimal. In this article, I made use of climate change impacts and adaptation options to scrutinise the concept of climate justice in Africa. The article sought to establish whether or not climate justice has a place on the African continent. To achieve that objective, I critically assessed climate change impacts and options for adaptation in various African countries vis-à-vis climate justice. The study found that climate justice is a farce for Africa because climate disruptions affect nations differently and adaptive capacities differ as well. It also emerged that climate change-based impacts in Africa largely affect women and poor people. Lastly, the desire for profit among developed countries and climate-based organisations deters the urgency for climate justice across the globe.